The age and growth of hottentot seabream Pachymetopon blochii before and after the South African linefish state of emergency in 2000 - Farthing, MW; Winkler, AC; Anderson, K; Kerwath, S; Wilke, C; Potts, WM (African journal of marine science, 2018)
The hottentot seabream Pachymetopon blochii is a small-sized (maximum 2.67 kg) sparid endemic to southern Africa. It is an important target in South Africa's Western Cape traditional linefishery, particularly in the absence of more valuable pelagic species (such as Thyrsites atun and Seriola lalandi). In 2000, South Africa's linefishery was declared to be in a state of emergency, and commercial fishing effort was consequently reduced by 70%. A subsequent increase in stock biomass and intraspecific competition, coupled with environmental changes, were hypothesised to have thereafter altered the growth rate of hottentot, from 2000 to 2010. This study aimed to revise outdated age-growth models for the hottentot by using modern techniques (sectioned otoliths), and to compare age-growth relationships before and after the declared linefish state of emergency. The maximum age observed was 19 years, with no difference in the growth rate between sexes (p = 0.39-0.43) or time-periods (p = 0.96). Although the growth rate did not change, there is evidence that the age structure of the stock changed between time-periods as a result of changes in fishing pressure between 2000 and 2010. The enhanced recent growth model for hottentot, described as L t = 418.063 (1 - e −0.104(t - [−4.709]) ) (pooled sexes; n = 206), indicates a considerably slower growth rate for this species than was proposed previously using whole otoliths and has major implications for effective stock management.